1965
DOI: 10.4039/ent97887-8
|View full text |Cite
|
Sign up to set email alerts
|

Community Stability and the Strategy of Biological Control

Abstract: Canad. Ent. 97: 887-895 (1965) Community organization is defined as the mean number of trophic links connecting species of different trophic levels in a community. For the special purposes of this paper, competition is assumed to occur whenever two species are known to eat the same food species. Community stability is defined as the reciprocal of the mean, for all species, of the standard error of logarithms of annual collection sizes. It is thus a measure of stability over time of the species populations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(35 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…Some have suggested that interspecific interference may cause the combined effect of multiple enemy species to be less than the effect of the single most efficient enemy species (Turnbull and Chant 1961, Watt 1965, Kakehashi et al 1984. -A second controversial issue in biological control is whether it is a better strategy to introduce a single "best" enemy species or whether several natural enemy species should be introduced for greatest effect.…”
Section: Three Issues Motivating This Studymentioning
confidence: 99%
“…Some have suggested that interspecific interference may cause the combined effect of multiple enemy species to be less than the effect of the single most efficient enemy species (Turnbull and Chant 1961, Watt 1965, Kakehashi et al 1984. -A second controversial issue in biological control is whether it is a better strategy to introduce a single "best" enemy species or whether several natural enemy species should be introduced for greatest effect.…”
Section: Three Issues Motivating This Studymentioning
confidence: 99%
“…Predation and parasitism are the cornerstones of biological control (DeBach, 1964), but there is no consensus on the role of competition in biological control. Some researchers contend that species interactions through (within-guild) interspecific competition may reduce pest suppression (Ehler, 1985;Force, 1974;Watt, 1965); whereas others have demonstrated species interactions that led to better pest density suppression, as a result of complementary actions (Huffaker & Kennett, 1966;Huffaker, 1986). The importance of mutualism in biological control is observed primarily when predation and/or parasitism of homopterans are reduced when homopterans are tended by ants (Hölldobler & Wilson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Fertiliser perturbation of a field which had been abandoned for 16 years was found to cause a surge in herbivorous pests. A survey in Canadian forests has shown that simple parasitoid complexes may lead to greater stability of Lepidoptera than larger complexes which share more intense competition (Watt, 1965) and, under very controlled laboratory conditions, an aquatic protozoan (Paramecium) was kept more stable if the number of its competitor species for food or its predator species was reduced (HairstOn et al, 1968). The stabilityof species abundance and composition from year to year of three fields in Michigan with the same history of abandonment was inversely related to diversity (Murdoch et al, 1972).…”
Section: Diversity and Stabilitymentioning
confidence: 99%